2018
DOI: 10.1002/jobm.201700506
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhization of Tricholoma matsutake with Quercus aquifolioides affects the endophytic microbial community of host plant

Abstract: Tricholoma matsutake (S. Ito et Imai) is an ectomycorrhizal basidiomycete associated with Pinaceae and Fagaceae trees in the Northern Hemisphere. It is still unknown whether the symbiotic relationship with this ectomycorrhiza could affect the host plant's endophytic microbial community. In this study, we used high throughput sequencing to analyze the endophytic microbial communities of different Quercus aquifolioides tissues with or without T. matsutake partner. About 35,000 clean reads were obtained per sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The molecular screening of 16S rDNA libraries (Boer et al 2005) revealed that a wide repertoire of microbes, including OTUs belonging to the genera Burkholderia, Bacillus, Mycobacterium and Paenibacillus, were significantly more abundant when matsutake was more abundant in soil (Oh et al 2016). The genus Pseudomonas was also found to be abundant in the mycorrhizal roots of T. matsutake sampled from another region (Li et al 2018). The observations do not allow us, however, to generalize any common features of the bacterial community in matsutake shiro soil.…”
Section: Introductionmentioning
confidence: 76%
“…The molecular screening of 16S rDNA libraries (Boer et al 2005) revealed that a wide repertoire of microbes, including OTUs belonging to the genera Burkholderia, Bacillus, Mycobacterium and Paenibacillus, were significantly more abundant when matsutake was more abundant in soil (Oh et al 2016). The genus Pseudomonas was also found to be abundant in the mycorrhizal roots of T. matsutake sampled from another region (Li et al 2018). The observations do not allow us, however, to generalize any common features of the bacterial community in matsutake shiro soil.…”
Section: Introductionmentioning
confidence: 76%